2010
DOI: 10.1007/s10803-010-0960-8
|View full text |Cite
|
Sign up to set email alerts
|

Scalar Inferences in Autism Spectrum Disorders

Abstract: On being told "John or Mary will come", one might infer that not both of them will come. Yet the semantics of "or" is compatible with a situation where both John and Mary come. Inferences of this type, which enrich the semantics of "or" from an 'inclusive' to an 'exclusive' interpretation, have been extensively studied in linguistic pragmatics. However, the phenomenon has not been much explored in Autism Spectrum Disorders (ASDs), where pragmatic deficits are commonly reported. Here, we present an experiment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(94 citation statements)
references
References 64 publications
10
80
1
3
Order By: Relevance
“…Norbury, 2005a, b). In line with this suggestion, an increasing number of studies have highlighted that individuals with ASD and age appropriate language scores perform comparably to age-matched TD peers on pragmatic tasks (Norbury, 2005a,b;Pijnacker et al, 2009;Chevallier et al, 2010). Comparing rates of over-and under-informative utterances in different clinical groups will yield novel insights into the underlying skills that support communicative competence.…”
Section: Discussionmentioning
confidence: 95%
“…Norbury, 2005a, b). In line with this suggestion, an increasing number of studies have highlighted that individuals with ASD and age appropriate language scores perform comparably to age-matched TD peers on pragmatic tasks (Norbury, 2005a,b;Pijnacker et al, 2009;Chevallier et al, 2010). Comparing rates of over-and under-informative utterances in different clinical groups will yield novel insights into the underlying skills that support communicative competence.…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, it has been demonstrated that children with ASD perform as well as TD peers on the ability to detect pragmatic violations, such as utterances that are literally true but pragmatically under-informative (e.g., “ some of the apples are inside the boxes ” when shown a picture where all of the apples are inside the boxes), and that higher verbal IQ scores predicted higher sensitivity to under-informativeness within the ASD group (Chevallier et al, 2010). Similar conclusions are reached in studies with an adult ASD population (Pijnacker et al, 2009).…”
Section: Potential Causes Of Pragmatic Difficulties In Asdmentioning
confidence: 99%
“…Sensitivity to informativeness, as tested by Chevallier et al (2010), Katsos et al (2011), and Pijnacker et al (2009) is a case in point of “linguistic-pragmatics.” For example, in order to reject pragmatically infelicitous sentences of a speaker saying that “ some of the apples are inside the boxes ” (given a picture in which all of the apples are inside the boxes), a child need to draw on vocabulary knowledge (a child who has mastered the semantic meaning of “some” and “all” will know that “all” is a more informative expression), together with sensitivity to the pragmatic maxim that instructs speakers to avoid being under-informative. However, demands on ToM are minimal, because the knowledge that is necessary to evaluate if the utterance is informative or not is visually accessible and shared between the child and the speaker.…”
Section: Two Different Pragmatic Skills: Linguistic- Vs Social-pragmmentioning
confidence: 99%
“…Second, despite an explosion of behavioral experiments on scalar implicature (Barner, Brooks, & Bale, 2010; Bonnefon et al, 2009; Bott & Noveck, 2004; Breheny, Ferguson, & Katsos, 2012; Chemla & Spector, 2011; Chevallier et al, 2008; Chevallier, Wilson, Happé, & Noveck, 2010; De Neys & Schaeken, 2007; Feeney, Scrafton, Duckworth, & Handley, 2004; Goodman & Stuhlmuller, 2013; Foppolo, Guasti, & Chierchia, 2012; Grodner et al, 2010; Huang & Snedeker, 2009a, 2009b, 2011; Marty, Chemla & Spector, 2013; Noveck, 2001; Papafragou & Musolino, 2003; Papafragou & Tantalou, 2004; Papafragou, 2006; Pouscoulous, Noveck, Politzer, & Bastide, 2007) relatively little is known about the neural computation of scalar implicature. Two studies have investigated the brain response produced when a scalar implicature conflicts with world knowledge.…”
Section: Overview Of the Experimentsmentioning
confidence: 99%